Protection Efficacy of the rLTB-R1 Chimera against Experimental Swine Mycoplasmal Pneumonia - Alves Ferreira, Marcos Roberto; Fonseca Finger, Paula; Georg Magalhães, Carolina; Pouey da Cunha, Carlos Eduardo; Moreira Júnior, Clóvis; Deon Kich, Jalusa; Morés, Nelson; Nunes Moreira, Ângela; Antônio Dellagostin, Odir; Rochedo Conceição, Fabricio (Acta Scientiae Veterinariae, 2019)
Background: Mycoplasma hyopneumoniaeis the etiological agent of the Swine Mycoplasmal Pneumonia (SMP), one of the most economically significant diseases in the swine industry worldwide. Commonly used vaccines for SMP control consist of inactivated whole cells (bacterins). These vaccines are efficacious against M. hyopneumoniaechallenge, but do not prevent colonization by the pathogen or completely eliminate pneumonia. P97 adhesin is conserved in the M. pneumoniae virulent strains, therefore it is an attractive target to be used in recombinant vaccines against M. hyopneumoniae. The aim of the present study was to evaluate protection afforded by rLTB-R1, a recombinant chimera composed by LTB fused with the R1 repeat region of P97 adhesin of M. hyopneumoniae, in specific-pathogen-free (SPF) piglets vaccinated by intranasal or intramuscular route and challenged with a pathogenic strain of M. hyopneumoniae. Materials, Methods & Results:PCR products of the LTB and R1 coding sequences were fused, then cloned into pETDEST42™ expression vector. The rLTB-R1 was expressed in Escherichia coli BL21 (DE3) Salt induction (SI).They were allocated into three groups: four piglets were intranasally vaccinated with 1 mg of rLTB-R1 solubilized in 1 mL of PBS at 0 and 14 days (IN rLTB-R1 group); four piglets were intramuscularly vaccinated with 1 mg of rLTB-R1 solubilized in 1 mL of PBS at 0 and 14 days (IM rLTB-R1 group);three piglets were intranasally and intramuscularly inoculated with 1 mL of PBS (control group).Two weeks after the last immunization (28 day), piglets were intratracheally challenged with 10 mL of a suspension containing 109color-changing unit (CCU) of pathogenic M. hyopneumoniae 7448 strain on three consecutive days. Until the challenge (28 days), intranasal and intramuscular vaccination with rLTB-R1 induced seroconversions of anti-R1 systemic antibodies of 1.6 and 4.6 ×, respectively. The IN rLTB-R1 group had no pulmonary lesion, rLTB-R1 conferred protection against experimental SMP. On the other hand, IM rLTB-R1 and control groups had on average 7.24% and 8.46% of pulmonary lesion, respectively, showing that intramuscular vaccination with rLTB-R1 did not confer protection. Discussion:The rLTB-R1, when intranasally administrated to mice, elicited production of anti-R1 IgA in trachea and bronchi as well as specific Th1 response, suggesting an adequate stimulation of the mucosal immune system. We believe that rLTB-R1 induced a similar immune response in piglets intranasally vaccinated, conferring protection against experimental SMP. The present study, the rLTB-R1 alone, without any chemical adjuvant, stimulated a significant seroconversion of anti-R1 systemic antibodies in pigs intramuscularly vaccinated, showing the potential of LTB as a parenteral adjuvant in swine vaccination.Previous work has shown that the intramuscular administration route was evaluated in pigs because mice intramuscularly vaccinated with rLTB-R1 presented significant levels of anti-R1 IgA in trachea and bronchi, suggesting that rLTB can stimulate some degree of mucosal immunity even if not delivered by a mucosal route.However, in the present study, piglets intramuscularly vaccinated with rLTB-R1 presented high levels of anti-R1 systemic antibodies, they were not protected.On the other hand, intranasal vaccination of piglets with rLTB-R1 elicited low levels of anti-R1 systemic antibodies (1.6 × at 28 days), but it conferred full protection against experimental SMP. The present study demonstrated that intranasal vaccination of piglets with rLTB-R1 conferred protection against experimental SMP. A more detailed analysis of the protective immune response induced by rLTB-R1 in pigs is currently being performed.